Desarrollo de un modelo de cadena de valor para el sector productivo maderero de muebles para acabados de la construcción, como mecanismo de integración de las pequeñas y medianas empresas (Pymes), ubicadas en el sector norte de la ciudad de Quito, afiliadas a la Camara de la Pequeña y mediana empresa de Pichincha ( CAPEIPI ) - Chirau Daquilema, Laura María (2015)
This research is focused on developing a value chain model as an integration tool for small and medium enterprises from wood productive areas, which main activity is manufacturing furniture for buildings finishing, a theorical research is the point of start an it has relation with strategic administration, mainly focusing in SWOT chart and related strategies; the present situation for Ecuadorian PYMES and value chain theory specifically based on Michael Porter model. Building sector discussion takes place aimed to show the state development that Quito has especially during last years, determining that the majority of housing projects are located in the north side of the city. This research shows that PYMES related with furniture manufacturing for building finishes as: kitchens, closets, bathrooms and offices, has a low administrative and productive level, along with low interest in showing an improvement of technology; production processes, training staff and lack of PYMES integration among the same productive sector, so that their participation in macro markets in minimal. Facing this situation, a value chain model is proposed as an integration method between PYMES and chain related enterprises; focused mainly to improve their productive processes indeed with environmental responsibility, since raw material enters to the process until the final good is delivered to the customer; which will be told apart with added value; to establish alliances with cooperation and integration compromises among PYMES from the same sector, suppliers and customers and in this way, to reach the expected growing and market positioning.